2021
DOI: 10.3390/catal11050605
|View full text |Cite
|
Sign up to set email alerts
|

Multienzymatic Processes Involving Baeyer–Villiger Monooxygenases

Abstract: Baeyer–Villiger monooxygenases (BVMOs) are flavin-dependent oxidative enzymes capable of catalyzing the insertion of an oxygen atom between a carbonylic Csp2 and the Csp3 at the alpha position, therefore transforming linear and cyclic ketones into esters and lactones. These enzymes are dependent on nicotinamides (NAD(P)H) for the flavin reduction and subsequent reaction with molecular oxygen. BVMOs can be included in cascade reactions, coupled to other redox enzymes, such as alcohol dehydrogenases (ADHs) or en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 103 publications
0
29
0
Order By: Relevance
“…Due to the growing emphasis on sustainable large-scale production of chemicals and pharmaceuticals, enzymatic processes, particularly those associated with redox enzymes, have gained traction over the years as reflected in several recent Review articles. [37][38][39][40] For NAD(P)-coupled redox enzymes, cofac-tor regeneration is essential for practical implementation. Two modes of enzymatic regeneration are (i) substrate-coupled and (ii) enzyme-coupled reactions.…”
Section: Types Of Enzymatic Regeneration Methodsmentioning
confidence: 99%
“…Due to the growing emphasis on sustainable large-scale production of chemicals and pharmaceuticals, enzymatic processes, particularly those associated with redox enzymes, have gained traction over the years as reflected in several recent Review articles. [37][38][39][40] For NAD(P)-coupled redox enzymes, cofac-tor regeneration is essential for practical implementation. Two modes of enzymatic regeneration are (i) substrate-coupled and (ii) enzyme-coupled reactions.…”
Section: Types Of Enzymatic Regeneration Methodsmentioning
confidence: 99%
“…In particular, cyclohexanone monooxygenase (CHMO) has been extensively investigated for the synthesis of ε-caprolactone, an important precursor for polymer synthesis (Schmidt et al, 2015;Scherkus et al, 2016;Engel et al, 2019a). Generally, most cascades have been developed by coupling various alcohol dehydrogenases (ADHs) (Bornadel et al, 2015;Schmidt et al, 2015;Scherkus et al, 2016;Scherkus et al, 2017;Engel et al, 2019b;de Gonzalo and Alcántara, 2021) as well as newly reported thioredoxin/thioredoxin reductases pairs (Zhang et al, 2022) with CHMO to form redox-neutral self-sufficient systems. Despite these advances, in most one-pot systems, substrate concentrations have been used up to 100 mM given the strong substrate and product inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Ketone 1c is oxidized to 2b and to 4-oxahomoadamantane-5-one (lactone 2c) (Bayer-Williger reaction) [22,23].…”
Section: Introductionmentioning
confidence: 99%